A Validation Study of a Subjective and Objective Socioeconomic Status Scale - Hawley, Lisa D (ILIN Education Indonesia, 2025)
Objectives: The purpose of this study is to validate a subjective and objective socioeconomic measure to enhance research and clinical applications of socioeconomic (SES) constructs. To further understand the measurement of Socioeconomic Status (subjective and objective) in counseling, two main research questions are investigated. First, would objective indicators of SES (education, income, etc..) result in a separate construct from subjective indicators of SES (perceived SES, etc..) using social positioning and comparison items? Second, would the objective and subjective items correlate with the Macarthur’s Scale SES? Methods: A Delphi Method was employed to develop a socioeconomic status with both objective and subjective SES items. The measure consists of 33 items including demographics (5), subjective (18), objective (2) SES status subscale and mental health (8) subscale. Two samples (N=455) were analyzed using Exploratory Factor Analysis (EFA). Results: The EFA’s resulted in a three-factor solution: perception of SES; perception of one’s ability to change their SES; and, objective SES. Conclusions: This study is consistent with the literature suggesting that objective and subjective SES are distinct variables. Improved methods and increased use of SES measures accounting for subjective and objective SES is needed.